A comparison of the accuracy of the CapitalBio Mycobacterium real-time polymerase chain reaction and the Xpert MTB/RIF assay for the diagnosis of tuberculous meningitis. (March 2021) - Sun, Lihua; Yao, Liwei; Fu, Genlian; Lin, Lihua; Zhu, Enlan; Huang, Jinpeng
Highlights: The early diagnosis of tuberculous meningitis (TBM) is difficult. We investigated the efficiency of the CapitalBio Mycobacterium real-time PCR detection test for TBM was tested. The diagnostic efficiency of the CapitalBio detection test for TBM was similar to that of the Xpert MTB/RIF system. Abstract: Objectives: We aimed to compare the efficiency of the CapitalBio Mycobacterium real-time polymerase chain reaction (PCR) detection test with the standard Xpert MTB/RIF assay for the diagnosis of tuberculous meningitis (TBM). Methods: We analyzed cerebrospinal fluid (CSF) from 163 patients with suspected TBM that were collected between January 1, 2018, and December 31, 2019. For both tests, we determined the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the curve (AUC). Next, we compared the diagnostic accuracy of the two techniques using clinical diagnosis as a reference standard. Results: The sensitivity, specificity, PPV, NPV, and AUC, of the CapitalBio Mycobacterium detection test were 48.5%, 100%, 100%, 29.6%, and 0.74, respectively, when used for the diagnosis of TBM. In comparison, the Xpert MTB/RIF assay returned values of 47.0%, 100%, 100%, 29.0%, and 0.74, respectively. Our analysis showed that the diagnostic accuracies of the CapitalBio Mycobacterium detection test and the Xpert MTB/RIF assay were very similar; the accuracy of both tests for detecting mycobacteria was significantly higher than that associated with acidfast staining. Conclusions: The CapitalBio Mycobacterium real-time PCR detection test has moderate sensitivity and very high specificity for TBM; results are very similar to those generated by the Xpert MTB/RIF assay. We recommend that the CapitalBio PCR test should be used as an initial screening method for TB.